Pendidikan Karakter Berbasis Nilai Integritas dan Anti-Korupsi: Telaah Pemikiran dan Praktik Kenegaraan Denny Indrayana dalam Perspektif Pendidikan Agama Islam - Rizky Firnanda; Muhammad Ahsan Sachrawi; Annisa Nur Asyiah; Fathya Shafa Diani (Lembaga Yasin AlSys, 2026)
Character education based on integrity and anti-corruption values is an urgent necessity amid the continued prevalence of corrupt practices across various sectors of life. This condition underscores the importance of strengthening students’ character through education that instills honesty, responsibility, and moral awareness from an early age. This study aimed to analyze Denny Indrayana’s ideas and state governance practices concerning integrity and anti-corruption values and their relevance to Islamic Religious Education (PAI). This study employed a qualitative approach using the literature review method. Data were obtained from books, scholarly journals, articles, and works by Denny Indrayana addressing integrity, law enforcement, good governance, and corruption eradication. The data were analyzed descriptively and analytically through the stages of data reduction, data presentation, and conclusion drawing. The results showed that Denny Indrayana’s ideas position integrity, honesty, accountability, transparency, and moral courage as the principal foundations for realizing clean and corruption-free governance. These values are strongly relevant to the principles of PAI, namely trustworthiness, sidq (honesty), justice, responsibility, and ihsan. This alignment indicates that integrity and anti-corruption values can be internalized through PAI instruction to develop students who possess ethical character and moral commitment. This study concludes that Denny Indrayana’s ideas are relevant as a conceptual foundation for developing character education based on integrity and anti-corruption values. Integrating these values into PAI instruction has implications for strengthening a sustainable anti-corruption culture in educational settings and society.